2017
DOI: 10.1016/j.ijfatigue.2016.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Relation between crack growth behaviour and crack front morphology under hold-time conditions in DA Inconel 718

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. This is an author-deposited version published in : http://oatao.univ-toulouse.fr/ Eprints ID : 18105To link to this article : a b s t r a c tThe crack growth behaviour of Direct Aged Inconel 718 was studied at 550°C. Experiments were carried out under pure fatigue cycles, hold-time cycles of different durations and a mix of both. Hold-time cycles were systematically assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…To quantify fatigue crack propagation behavior, the following three features of the 3D crack were measured: crack opening displacements (CODs), the extent of secondary cracks, and uncracked bridging ligaments (which refers to the uncracked regions between two crack segments). In addition, due to the complexity of the crack tip, especially at elevated temperatures in air under dwell-fatigue conditions [21,26], the crack tip has now been defined as "the tip of the continuous and fully opened crack" and the discontinuous cracking zone is considered to be the region ahead of the continuous crack tip with discontinuous cracks to allow more precise description (and clarity) in this paper.…”
Section: X-ray Ct: Image Processing and Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…To quantify fatigue crack propagation behavior, the following three features of the 3D crack were measured: crack opening displacements (CODs), the extent of secondary cracks, and uncracked bridging ligaments (which refers to the uncracked regions between two crack segments). In addition, due to the complexity of the crack tip, especially at elevated temperatures in air under dwell-fatigue conditions [21,26], the crack tip has now been defined as "the tip of the continuous and fully opened crack" and the discontinuous cracking zone is considered to be the region ahead of the continuous crack tip with discontinuous cracks to allow more precise description (and clarity) in this paper.…”
Section: X-ray Ct: Image Processing and Quantificationmentioning
confidence: 99%
“…Conventionally, FCP rate has been measured by a direct current potential drop (DCPD) method, which is a measurement of the overall averaged crack length of the through-cracked area [20,21]. It is usually observed that the FCP rate can be 2~3 orders of magnitude higher in the oxidising environment than that in vacuum or an inert atmosphere [4,6,11,[22][23][24], even though the DCPD method usually underestimates the crack length and the accuracy of the DCPD measurement is biased by crack front curvature and tortuosity (especially in the case where oxidation-assisted FCP is dominant, due to crack branching at the propagating intergranular crack tip or micro-cracking processes ahead of the crack tip with interlinked uncracked ligaments) [21,25,26]. This enhanced FCP is usually associated with the dwell period either at the maximum or minimum load employed during the test and the test temperatures in an oxidising environment [5,6,13].…”
Section: Introductionmentioning
confidence: 99%
“…Fessler et al, that for very complex crack tip shapes, crack tip area with local "longer crack" than other areas will induce lower SIF values and subsequently lower FCGR [37]. Alternatively, the "shortest" local crack could induce increase in SIF values and subsequently higher FCGR [37]. Unfortunately, the test set-up prevents from such an analysis.…”
Section: Discussionmentioning
confidence: 99%
“…But for biaxial testing, using a non-standard specimen geometry and complex prescribed loadings, a similar approach was not possible. Moreover, experimental results revealed very complex 3D crack geometries, making the analysis of SIF and SIF influence on FCGR a prerequisite to a reliable model development [37]. In this respect, a complementary numerical modeling study has been carried out using the Z-set finite element analysis suite.…”
Section: Modeling Fatigue Crack Growth Ratesmentioning
confidence: 99%
“…Initiated by Ritchie and Bathe and followed by Hicks and Pickard, this approach only requires the knowledge of the crack path. Taking into account the front curvature is then possible as described by Fessler et al…”
Section: Methodsmentioning
confidence: 99%